2013
DOI: 10.1515/jpm-2012-0296
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of PPROM with anhydramnion in humans: first experience with different amniotic fluid substitutes for continuous amnioinfusion through a subcutaneously implanted port system

Abstract: Objective: This study aims to treat patients with preterm premature rupture of the membranes (PPROM) and anhydramnion using continuous amnioinfusion through a subcutaneously implanted port system. Methods: An amniotic fluid replacement port system was implanted in seven patients with PPROM and anhydramnion starting at the 20 th week of gestation (range, 14-26 weeks) for long-term amnioinfusion. Saline solutions (2 L/day; Jonosteril ® , Sterofundin ® , isotonic NaCl 0.9% solution, lactated Ringer's solution) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…The continuous long-time amnio-infusion through a subcutaneously implanted port system is a method to establish a chronic lavage of the amniotic cavity (Figure 4) [66][67][68]. A subcutaneous pouch for the port capsule is prepared under local anesthesia.…”
Section: "Flush Out" Methods For the Treatment Of Classic Pprommentioning
confidence: 99%
See 4 more Smart Citations
“…The continuous long-time amnio-infusion through a subcutaneously implanted port system is a method to establish a chronic lavage of the amniotic cavity (Figure 4) [66][67][68]. A subcutaneous pouch for the port capsule is prepared under local anesthesia.…”
Section: "Flush Out" Methods For the Treatment Of Classic Pprommentioning
confidence: 99%
“…Gratacos et al did not find any evidence of spontaneous membrane healing after fetoscopy in humans suggesting that the membrane defect persists until delivery [33]. Recent studies found that there is a relationship between the access hole size and the rate of PPROM as a complication of fetoscopic surgery [68,72]. We demonstrated a four-fold reduction in the rate of the access trauma of chorio-amniotic membranes by application of smaller fetoscopic devices with a 1 mm flexible optic [66], however, the risk of PPROM before 32/0 weeks could not be reduced to less than 10% of our cohort [67].…”
Section: Genetic and Iatrogenic Factors (A) Genetic Componentsmentioning
confidence: 99%
See 3 more Smart Citations